In Memory of Fahire Battalgazi; Bringing Back a Fish Collection to Life - Özcan Gaygusuz; Müfit Özuluğ; Çiğdem Gürsoy Gaygusuz; Zeynep Dorak; Gülşah Saç; Elif Ece Serezli (Turkish Journal of Bioscience and Collections)
Istanbul University (I.U.) plays an important role in handing down the valuable to the next generations by protecting its scientific and cultural assets with the museums it possesses. Fish collection have inherited from I.U. Hydrobiology Institute to I.U. Faculty of Aquatic Sciences and preserved until today in I.U. Faculty of Aquatic Sciences, Inland Fisheries Production and Research Unit located in Sapanca (Sakarya, Turkey). In course of time, the protective liquid of fish material has begun to evaporate from the jars; or they have somehow lost their efficiency in protection. For this reason, it was aimed to recover this collection, which contains rare samples from Turkish seas and freshwater habitats, to update the jar labels, and to replenish the preservative fluids. During this venture, we came across some fish samples that were collected and examined by Prof. Dr. Fahire Battalgazi, the first Turkish woman ichthyologist, who occupies an important position in the history of science of Turkey. Here, we introduce the fish species (Alburnus kotschyi, Capoeta barroisi, C. trutta, Carasobarbus luteus, Garra kemali, Gobio microlepidotus, G. insuyanus, Oxynoemacheilus eregliensis, Petroleuciscus borysthenicus, Squalius fellowesii and Vimba vimba) collected and/or examined by Prof. Dr. Fahire Battalgazi and labeled with her own handwriting.